2021
DOI: 10.3390/foods10040902
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Role of Probiotics in Protection against Influenza a Virus Infection in Mice

Abstract: Influenza A virus induces severe respiratory tract infection and results in a serious global health problem. Influenza infection disturbs the cross-talk connection between lung and gut. Probiotic treatment can inhibit influenza virus infection; however, the mechanism remains to be explored. The mice received Lactobacillus mucosae 1025, Bifidobacterium breve CCFM1026, and their mixture MIX for 19 days. Effects of probiotics on clinical symptoms, immune responses, and gut microbial alteration were evaluated. L. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 46 publications
2
23
0
Order By: Relevance
“…Gut microbiome alterations, with the depletion of butyrate-producing bacteria, have been documented in SARS-CoV-2 infection, and in most patients with severe COVID-19 [ 14 , 15 , 16 ]. These data are not unexpected, since butyrate exerts a pivotal role in protecting the human body against infections and inflammation [ 21 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gut microbiome alterations, with the depletion of butyrate-producing bacteria, have been documented in SARS-CoV-2 infection, and in most patients with severe COVID-19 [ 14 , 15 , 16 ]. These data are not unexpected, since butyrate exerts a pivotal role in protecting the human body against infections and inflammation [ 21 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that in the human intestine, Adlercreutzia species can convert resveratrol to dihydroresveratrol (Bode et al 2013 ). Influenza A virus-infected mice treated with Lactobacillus mucosae 1025 and Bifidobacterium pumilus CCFM1026, exhibited increases in the relative abundance of Adlercreutzia , Lactobacillus , and Bifidobacterium , and modulation of short-chain fatty acid metabolism, leading to enhanced production of butyrate (Lu et al 2021 ). We thus consider that the anti-inflammatory effect of BLa80 may be associated with changes in the gut microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…Probiotics have been reported to regulate butyrate metabolism resulting in an enhancement of host resistance to influenza virus infection. The correlation analysis revealed that the butyrate was negatively related to viral loading ( Lu et al., 2021 ). SCFAs produced by probiotics are also potential regulatory effectors of epithelial proliferation in the gut ( Wang et al., 2018 ).…”
Section: Probiotics Contribute To the Chemical Barrier To Exert Antiv...mentioning
confidence: 99%